Gender Representation in Iranian Lifestyle Magazine, Green Family: A Semiological Analysis - Shasavandi, Leila (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Gender representation in the media is an area of gender and media studies that has enjoyed adequate scholarly attention. A slew of the studies conducted in this area have highlighted and explored issues in respect to image, stereotypes, inequality and how the media portrayals can help reinforce and develop them. This study examines the gender representation in advertisements in Iranian lifestyle magazine, Green Family, a highly circulated magazine in Iran. The study focused on a span of two years (2014-2016) period and it systematically investigates the gender representations in Green Family using semiotic analysis, textual analysis and Goffman‟s frame analysis. Result shows that six highly repeated themes of gender representations were identified: the invisible beauty of women; gender roles in the family; parenthood of women vs men; gender representation in advertisements of health, self-caring products; public vs private dichotomy. The representations of men and women roles were distinctly stereotypical. Women were mostly domesticated (homemaking, cooking, and child care) while on the flip side, men were mostly shown in the public places. They were represented in professional positions, mostly tech-savvy and as a fun parent. Furthermore, women were presented mostly in hijab; the depictions of the Westernized facial beauty of women were also mostly used in those advertisements. The study also found that women were presented more in health products more than men. Keywords: Advertisement, gender, representation, semiotic, textual analysis, Green Family magazine.

ÖZ : Medyada toplumsal cinsiyetin temsili daha özel de kadınların temsili üzerine çok sayıda çalışma yapılmıştır. Araştırmacılar toplumsal cinsiyetin medyada nasıl temsil edildiğini ve toplumda nasıl görül düğünü anlamaya çalıştılar. Bu çalışma iki yıllık süre içinde (2014-2015) İran‟daki magazine dergilerinden The Green Family‟de reklamlarda toplumsal cinsiyetin nasıl temsil edildiğini analiz etmektedir. Çalışmada, semiyoloji ve metin analizini yanı sıra Goffman‟ın toplumsal cinsiyetin çerçevelenmesi analizi kullanılmıştır. Analizde reklamlarda sıklıkla tekrarlanan altı toplumsal cinsiyet temsili tanımlanmıştır. kadının görünmeyen güzelliği, aile içindeki toplumsal cinsiyet rolleri; kadının ve erkeğin ebeveyn rollerindeki temsili; öz bakım ürünleri ve sağlık ürünleri reklemlarında temsiliyet; özel ve kamusal ikiliği. Her bir kategoriye giren reklamlarda toplumsal cinsiyet farkı son derece görünürdür. Kadınlar özel alanda bakım işlerini yaparken temsil edilmişlerdir. Erkekler her zaman kamulsa landa , profesyoneller olarak, tekonoloji ile içiçe ya da eğlenceli ebeveynler olarak temsil edilmişlerdir. Kadınlar islemi giysiler içinde gösterilse de batılı yüz güzelliğinin temsiline öne çıkarıldığı görülmüştür. Çalışmada aynı zamanda sağlık ürünlerinin reklamlarında kadınların erkeklerden çok daha fazla kullanıldığı görülmüştür. Anahtarkelimeler: Reklam, toplumsal cinsiyet, temsil, semiyoloji, metin analizive magazin dergileri.
Master of Arts in Communication and Media Studies. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Assoc. Prof. Dr. Hanife Aliefendioğlu.
Keywords: Communication and Media Studies; Mass media and Gender Representation - Iran; Gender in mass media - Magazines Green Family; Advertisement; gender; representation; semiotic; textual analysis; Green Family magazine